OPTIMALISASI PROGRAM BIMBEL LITERASI SEBAGAI STRATEGI MENGURANGI KESULITAN MEMBACA DI SEKOLAH DASAR - Nurhalisa Nurhalisa; Moh. Wahyudi; Theopilus C. Motoh (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Education in Indonesia continues to develop, but still faces serious challenges, particularly low literacy rates among elementary school students. International data such as PISA 2019 shows that Indonesia's reading scores are at the bottom of the rankings, which is reinforced by other literacy surveys. Low reading interest and basic reading skills have a direct impact on learning success and the quality of national education. This community service aims to improve the literacy skills of elementary school students through a literacy tutoring program implemented in Bambapun Village, specifically for students of SDN 1 and SDN 3 Bambapun. The method used was tutoring with an individual, creative, and systematic approach. The program was carried out for one week with three meetings held after Maghrib prayers at the Bambapun village KKN post, using simple facilities in the form of a room and student reading books. The results showed a significant improvement in students' reading skills, both in terms of technical aspects, fluency, and reading comprehension. In addition, there was an increase in students' motivation and interest in reading, which was reinforced by the support of parents and teachers. Thus, the literacy tutoring program proved to be effective in reducing reading difficulties and can be used as an alternative strategy to improve the quality of basic education in Indonesia.